Program Pendampingan Pengelolaan Risiko dalam Kewirausahaan Kolaboratif UMKM Kampoeng Aseupan dan UMKM Anyaman Bambu: indonesia - Sagita Triski, Dara; Muizu, Wa Ode Zusnita; Clementine, Marchella Grecia; Alifia, Alvita Rahma; Surbakti, Amelia Morina; Firstan, Rakha Zahran (UII, 2025)
Risk management in collaborative entrepreneurship in Kampoeng Aseupan MSMEs and Anyaman Bambu MSMEs through the Creative Art Space program is an important aspect in improving business sustainability. This Community Service (PPM) summarizes mentoring activities and Real Work Lectures (KKN) in Sukasari Village, which focus on risk analysis in collaboration between MSMEs. This Community Service (PPM) integrated KKN activity aims to assist MSME actors in recognizing and managing risks that arise in business collaboration, as well as strengthening collaborative capacity between business actors in Sukasari Village. The program is implemented through a participatory approach based on the Community Service (PPM) integrated Real Work Lecture (KKN) program and interactive facilitation sessions, such as surveys, in-depth interviews, and analysis of the Risk Assessment Matrix approach. Results of Community Service (PPM). From the results of the activity, it was found that the main challenges in MSME collaboration were the inconsistency of the cooperation agreement and the low involvement of consumers in the Creative Art Space program. As a solution, the team drafted a Memorandum of Understanding (MoU) document that regulates the rights and obligations of business partners and installed standing banners as a form of educational promotion. It is hoped that this effort can strengthen the effectiveness of cooperation and increase the competitiveness of MSMEs in a sustainable manner.